PELAKSANAAN PENGHAPUSAN BARANG MILIK DAERAH PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN TULANG BAWANG - M Nafiul Amri; Aladin Aladin; Husni Mubarok; Maulan Irwandi (Politeknik Negeri Sriwijaya, 2022)
This research was conducted at the office of the Regional Financial and Asset Management Agency of Tulang Bawang Regency. The purpose of this study was to analyze the implementation of the abolition of regional property and to find out the obstacles in the implementation of the abolition of regional property at the Office of the Regional Financial and Asset Management Agency of Tulang Bawang Regency. This type of research uses a qualitative descriptive approach. While the data collection techniques were carried out through the methods of observation, interviews, and documentation. Based on the research conducted, it can be seen that the main obstacle that hinders the implementation of the abolition of Regional Property at the Regional Financial and Asset Management Agency in Tulang Bawang Regency is the incompleteness of the documents proposed to be abolished. This is due to the lack of human resources (HR) in understanding the technical deletion at the Regional Work Unit office (SKPD).